2009
DOI: 10.1152/japplphysiol.00151.2009
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency assessment of airway and tissue mechanics in ventilated COPD patients

Abstract: Lorx A, Szabó B, Hercsuth M, Pénzes I, Hantos Z. Lowfrequency assessment of airway and tissue mechanics in ventilated COPD patients. J Appl Physiol 107: 1884 -1892, 2009. First published October 15, 2009 doi:10.1152/japplphysiol.00151.2009.-Low-frequency forced oscillations have increasingly been employed to characterize airway and tissue mechanics separately in the normal respiratory system and animal models of lung disease; however, few data are available on the use of this method in chronic obstructive pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…NPPV helps to reverse this process by augmenting VT and, potentially, reducing V9/Q9 mismatch via application of positive airway pressure. In an animal study, NEUMANN and HEDENSTIERNA [24] found improvement of V9/Q9 inhomogeneity during CPAP ventilation and, in COPD patients, LORX et al [25] evaluated airway and tissue mechanics using a low-frequency oscillation technique and observed improved homogeneity of ventilation in peripheral airways during application of increasing PEEP. The higher VT (and V9E) and greater airway pressure achieved with Hi-NPPV are probably responsible for the greater reversal of hypoventilation than with Li-NPPV, despite the greater air leaks associated with the higher inspiratory pressures.…”
Section: Discussionmentioning
confidence: 99%
“…NPPV helps to reverse this process by augmenting VT and, potentially, reducing V9/Q9 mismatch via application of positive airway pressure. In an animal study, NEUMANN and HEDENSTIERNA [24] found improvement of V9/Q9 inhomogeneity during CPAP ventilation and, in COPD patients, LORX et al [25] evaluated airway and tissue mechanics using a low-frequency oscillation technique and observed improved homogeneity of ventilation in peripheral airways during application of increasing PEEP. The higher VT (and V9E) and greater airway pressure achieved with Hi-NPPV are probably responsible for the greater reversal of hypoventilation than with Li-NPPV, despite the greater air leaks associated with the higher inspiratory pressures.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting inhomogeneous airways model is structurally analogous to a similar two-compartment model first described by Otis et al 2 , which compartmentalizes the lungs into ‘healthy’ and ‘diseased’ portions. However a more accurate description of lung mechanical behavior for many different pathologies may be obtained by distributing parallel heterogeneity across an arbitrary number of parallel pathways 1240118-120 . Such models allow for stochastic variability in R aw or H , depending on whether one seeks to ascribe the variation to airway or tissue heterogeneity, respectively.…”
Section: Inverse Modeling Of Impedancementioning
confidence: 99%
“…FOT analyses the pressure/flow responses of the airways to small forced oscillations delivered at the mouth, and has noticeable advantages over spirometry and plethysmography as it is effort independent, requires only tidal breathing and therefore can be carried out in children 3 , during sleep 4 and general anaesthesia 5 . Furthermore, FOT requires a shorter operator training.…”
Section: Introductionmentioning
confidence: 99%